Europe in figures. Eurostat yearbook 2010 (Luxembourg, 2010)
"Europe in figures – Eurostat yearbook 2010 – presents a comprehensive selection of statistical data on Europe. With just over 450 statistical tables, graphs and maps, the yearbook is a definitive collection of statistical information on the European Union. Most data cover the period 1998-2008 for the European Union and its Member States, while some indicators are provided for other countries, such as candidate countries to the European Union, members of EFTA, Japan or the United States. The yearbook treats the following areas: the economy; population; health; education; the labour market; living conditions and welfare; industry and services; agriculture, forestry and fisheries; trade; transport; environment and energy; science and technology; and Europe’s regions. This edition’s spotlight chapter covers national accounts statistics – with a particular focus on the economic downturn observed during 2008/2009"